Altered Tracer Distribution and Clearance in the Extracellular Space of the Substantia Nigra in a Rodent Model of Parkinson's Disease - Fang, Yuan; Dong, Yanchao; Zheng, Tao; Du, Dan; Wen, Jiexia; Gao, Dawei; Liu, Lanxiang (Frontiers in Neuroscience, 2017)
Abstract The relationship between extracellular space (ECS) diffusion parameters and brain drug clearance is not well studied, especially in the context of Parkinson’s disease (PD). Therefore, we used a rodent model of PD to explore the distribution and clearance of a magnetic resonance tracer. Forty male Sprague Dawley rats were randomized into 4 different groups: a PD group, a Madopar group (PD + Madopar treatment), a sham group, and a control group. All rats received an injection of the extracellular tracer gadolinium-diethylene triaminepentacetic acid (Gd-DTPA) directly into the substantia nigra (SN). ECS diffusion parameters including the effective diffusion coefﬁcient (D*), clearance coefficient (k’), ratio of the maximum distribution volume of the tracer (Vd-max%), and half-life (t1/2) were measured. We found that all parameters were significantly increased in the PD group compared to the other 3 groups (D*: F = 5.774, p = 0.0025; k’: F = 20.00, P < 0.0001; Vd-max%: F = 12.81, P < 0.0001; and t1/2: F = 23.35, P < 0.0001). In conclusion, the PD group exhibited a wider distribution and lower clearance of the tracer compared to the other groups. Moreover, k’ was more sensitive than D* for monitoring morphological and functional changes in the ECS in a rodent model of PD.